Комп’ютерні моделі динаміки пасажирських вагонів для швидкісного руху - Черняк, Ганна; Щербина, Юрій (КІНПАТРІ ЛТД, 2013)
The computer models of dynamics of the carriages for high-speed in software «Universal mechanism» are create with using approach MBS. The adequacy of each model is verified by comparing the maximum accelerations in horizontal and vertical directions of the car body and bogies, which defined in running dynamic tests and at simulation.
Computer models of dynamics of the carriages for high-speed